336 The effect of endometriosis on the prognosis of ovarian clear cell carcinoma: the jury is still out. (4th December 2020) - Buruiana, Felicia Elena; Tranoulis, Anastasios; Gupta, Bindiya; Balega, Janos; Singh, Kavita
Abstract : Introduction/Background: Women with endometriosis carry an increased risk for ovarian clear cell ovarian carcinoma (OCCC), also referred to as 'endometriosis-associated ovarian carcinoma'. Considered as the precursor lesion of a subset of OCCC, the prognostic role of endometriosis amongst women with OCCC remains a field of contention. Few studies have evaluated the prognostic significance of the concurrent endometriosis with conflicting results. The aim of this study was to ascertain the effect of endometriosis on the prognosis of OCCC. Methodology: This was a retrospective cohort study, from 2000 to 2019. Population-based prospectively collected data on OCCC with or without concurrent endometriosis were retrieved via the Pan-Birmingham Gynaecological Oncology database. Ninety-four women with a primary diagnosis of OCCC have been divided into groups based upon the detection of cancer arising from ovarian endometriosis (n=48, 51.1%) or not (n= 46, 48.9%) according to Samson and Scott criteria. Chi-squared test, t-test, and univariate/multivariate Cox regression were used. Survival curves were plotted via the Kaplan-Meier method, whilst survival differences were examined via the log-rank test for categorical variables or Cox regression for continuous variables. All reported p-values were two-tailed. Statistical significance was set at p-value <0.05. The statistical analysis was performed using Stata version 16.1 (Stata Corporation, TX, USA). Results: Women with OCCC arising from endometriosis had significantly lower levels of pre-operative CA-125 (434.63 ± 1135.57 Vs 867.30 ± 1609.67, p-value=0.02) and significantly lower incidence of post-operative residual disease (RD) (p-value=0.02). Age, post-menopausal status, FIGO stage and incidence of capsule rupture were not statistically significant. The mean overall survival (OS) and overall progression free survival (PFS) were 86.35 (95% CI 69.47 – 103.22) and 115.97 (95% CI 98.77 – 133.17) months, respectively. The presence of endometriosis did not affect neither the OS (87.99 Vs 75.30, p-value=0.25) nor the PFS (111.13 Vs 117.42, p-value=0.48). In univariate analysis, the FIGO stage II-IV and RD were correlated with poorer OS, whilst capsule rupture (CR) with poorer PFS. In multivariate analysis, FIGO stage [HR=2.86 (95% CI 1.47 – 5.55), p-value=0.002] and RD [HR=2.52 (95% CI 1.28 – 4.94, p-value=0.007) were found independent predictors for OS, whilst CR [HR=0.3 (95% CI 0.11 – 0.82), p-value=0.02] for PFS, respectively. No factors affected OS after stratification by stage. Conclusion: In this cohort concurrent endometriosis was not a predictive factor for the survival of OCCC women. Further studies are warranted to ascertain whether OCCC with or without coexisting endometriosis develop via distinct pathogenic pathways. Disclosures: Nil to disclose.